Community Psychiatry and the Medicalisation of Unemployment - Vella, Samuel (New Zealand Sociology, 2023)
This article discusses how the development of community psychiatry throughout the twentieth century has expanded the management of workers’ social lives through psy-professional techniques. I argue that the ideology of industrial psychology has promulgated a normative construction of mental health as an inner problem of the individual, and in doing so, has obscured the structural factors involved in the emotional lives of both employed and unemployed workers. Using the scholarship of Ralph, Illouz and Conrad, it is theorised that the medicalisation of structural unemployment constitutes an example of the continuation of the community psychiatry project in that it reproduces both the normative assumptions of the individual subject of the communicative model and acts to ameliorate the negative impacts of capitalist society experienced by workers through an activation ideology.